Diseño de un sistema de comunicación entre personas sordas y personas oyentes (2015)
This article presents the design of a software prototype, able to allow the communication between two languages, the voice and the signs language. It is pretended to decode both languages by using digital signal processing techniques as well as the establishment of common patterns. The goal is that a deaf person be able to understand what a hearing person says and vice versa.